Projeto pedagógico e currículo: percursos de construção e poder - Lopes, Rosana de Sousa Pereira (2010)
This research aims at analyzing how the school community recognizes the educational project and identifying how power relations are built on among members of the school community and educational project. These goals emerged from conducting field research in six schools of the state of Parana education involving teachers, students, parents, principals, teachers and staff. For the development of research, we adopted a qualitative approach, having as methodological parameter the content analysis. Seeking to achieve the proposed objectives and considering the evidence present in the information collected in the field, the research shows reflections on the pedagogical project, curriculum and collective construction, from power relations. We noticed that school communities express, through their beliefs, contributions, needs and achievements, a comprehension of teaching as a collective project and understand the school as a collective good; nevertheless, it should be emphasized that the concept of a collective expressed by the communities is permeated by ideologies, values and power relations which makes impossible recognize the pedagogical project as a tool and power of community yet. We still emphasize the fact that the educational project as a collective is not understood as a displacement process of power to the community, strategy for enhancement of people's right to decide about their lives